Exploration of Ethnomathematics: Mathematics Integration in Ngesti Swara Music in Jatisobo Village - Vemas Dwi Agustino; Herry Agus Susanto (Edumatica: Jurnal Pendidikan Matematika)
This article aims to explore how mathematics can be applied to Ngesti Swara art in Jatisobo Village. The method used in this research is qualitative with an ethnographic approach. The domain in this research is not limited. This means that every element of mathematics in this art will be explored. The algebraic domain, which discusses the application of sets in mathematics, and the geometry domain, which is studied from the shapes of the tools used in Ngesti Swara art performances, are the most explored domains. Still, these domains are not always the main thing and all elements of mathematics in culture will be discussed in this study. This research was conducted in Jatisobo Village the original place that still preserves this Ngesti Swara culture. This research is supported by Vygotsky's constructivist theory, which discusses social and neighborhood-based learning. The results showed that ethnomathematics is present in the Ngesti Swara art group in Jatisobo Village. This research also contributes to the field of education. Teaching using ethnomathematics as contextual learning can be a medium for learning mathematics. This research concludes that mathematics can be explored from the Ngesti Swara music culture in Jatisobo Village. This is one way to learn math while preserving culture.